PREDICTION THE SHELF LIFE OF COOKIES FORTIFIED WITH CATFISH (Pangasius hypopthalmus) PROTEIN CONCENTRATE USING DIFFERENT PACKAGING - Simanjuntak, May Kristina; Buchari, Dewita (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research aimed to predict the shelf life of cookies fortified with Catfish (Pangasius hypopthalmus) Protein Concentrate using aluminum foil and HDPE packaging coated with paperboard. The method used was Arrhenius with 25°C and 35°C of temperature storage. The parameters analyses were fat content and peroxide value. The results showed that based on the shelf life of cookies with aluminium foil in 25°C of temperature storage was 75.2972 days and for 35°C of temperature storage was 39.8896 days. HDPE packaging for 25°C of temperature storage was 45.5782 days and for 35°C of temperature storage was 13.8916 days.Keywords: Aluminium foil, Arrhenius, Cookies, HDPE, Shelf life